Development of Multidisiplin Integrated Project-Based Learning Model To Improve Critical Thinking and Cooperation Skills - Harli Trisdiono; Siswandari Siswandari; Nunuk Suryani; Soetarno Joyoatmojo (Jurnal Pendidikan Indonesia, 2019)
The development of a multidisciplinary integrated project-based learning model was carried out to answer the needs in elementary schools. Learning in elementary schools that use thematic approaches needs to be managed well to improve learning effectiveness. This study uses a type of research and development. The development process uses the Gall, Gall & Borg (2007) model. The preparation of guidelines and student book examples uses the steps of Dick, Carey, & Carey (2009). The model developed is accompanied by derivative products, namely learning manuals and student book examples. Based on this study, learning manuals and student book examples can be used in multidisciplinary integrated project-based learning to improve critical thinking skills and student collaboration.